2019
DOI: 10.1177/1049909119838974
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology Update: Low-Dose Naltrexone as a Possible Nonopioid Modality for Some Chronic, Nonmalignant Pain Syndromes

Abstract: Pain can have a devastating effect on the quality of life of patients in palliative medicine. Thus far, majority of research has been centered on opioid-based pain management, with a limited empirical evidence for the use of nonopioid medications in palliative care. However, opioid and nonopioid medications such as nonsteroidal anti-inflammatory drugs have their limitations in the clinical use due to risk of adverse effects, therefore, there is a need for more research to be directed to finding an alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
(73 reference statements)
0
23
0
1
Order By: Relevance
“…In low doses, naltrexone acts primarily through an alternate pharmacodynamic pathway and inhibits microglial activation, ultimately decreasing the inflammatory response [81]. Low-dose naltrexone has commonly been used for off-label treatment of autoimmune diseases, such as multiple sclerosis and inflammatory bowel disease [81]. Limited data exist, which are primarily case studies, regarding its use in CRPS or other chronic pain syndromes, such as fibromyalgia [81][82][83].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…In low doses, naltrexone acts primarily through an alternate pharmacodynamic pathway and inhibits microglial activation, ultimately decreasing the inflammatory response [81]. Low-dose naltrexone has commonly been used for off-label treatment of autoimmune diseases, such as multiple sclerosis and inflammatory bowel disease [81]. Limited data exist, which are primarily case studies, regarding its use in CRPS or other chronic pain syndromes, such as fibromyalgia [81][82][83].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Naltrexone is a reversible competitive antagonist with high affinity for MOR and KOR opioid receptors [29], in doses of 1-5 mg acts as a glial modulator reducing inflammation. In a dosing range at less than 1 μg per day, termed ultra low-dose (ULDN) it has been used for control of analgesia [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that low-dose naltrexone, an opiate receptor antagonist, may be effective, safe and inexpensive for adults FM [ 65 ]; yet, further large prospective controlled trials are needed before its use can be recommended for JPFS [ 66 ]. To our knowledge, no studies have been published regarding its use for the treatment of JPFS.…”
Section: Treatmentmentioning
confidence: 99%